God and the Covenant in the South African Wilderness - Templin, J. Alton (Church history, 1968)
When South African Prime Minister Hendrik Verwoerd was assassinated on September 6, 1966, a writer in the Cape Town Afrikaans newspaper, Die Burger, included an instructive comment. He said, “May the God in whom we believe make clear to us in His own good time what this terrible event is to signify to our country and her people.” This statement reminds us of a dimension in South African nationalism which goes beyond the normal interests of a nation. A theological motif is introduced which remains dominant in the South African mind. In the eyes of Afrikaners this theological concern lifts their problems out of the area of purely political and economic discussion for their whole cultural effort involves fulfilling a divine mission.2 Therefore, the death of Hendrik Verwoerd was more than a tragedy for the nation—it was a tragedy with divine implications.